Impact-resistant laminated glass and preparation process
By introducing a stress concentration layer and a stress diffusion layer into the window glass, forming a composite intermediate layer, and preparing impact-resistant laminated glass, it solves the problem that traditional window glass is difficult to break in extreme environments, and achieves faster glass breakage and passengers' safe escape.
Patent Information
- Application Number
- CN202411885148.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-20
AI Technical Summary
Traditional high-strength window glass is difficult to break quickly in extreme driving environments, forming an escape barrier and endangering the safety of passengers' lives.
A preparation process for impact-resistant laminated glass is adopted, including a first glass layer, a second glass layer and a composite intermediate layer. The composite intermediate layer is composed of a stress concentration layer, a stress diffusion layer and a third glass layer, and an impact-resistant laminated glass is formed by autoclave reaction.
While ensuring the safety of the vehicle, it can break the entire piece of glass from the inside faster in extreme driving environments, providing escape passages for personnel in the vehicle and protecting the safety of passengers' lives.
Smart Images

Figure CN119329141B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of laminated glass, and in particular to an impact-resistant laminated glass and a preparation process thereof. Background Art
[0002] Laminated glass is a kind of precision-constructed composite glass product, the core of which is that one or more layers of organic polymer interlayer (typically PVB film) are tightly embedded between two or more glass layers. This composite structure undergoes precision high-temperature pre-pressing treatment (or assisted by vacuum technology) and subsequent high-temperature and high-pressure processes to ensure that the glass and the interlayer form a permanent and firm bond.
[0003] In the construction of automobiles, windows are key safety components, and the selection and design of their glass materials are crucial, and they must strictly follow safety performance standards such as high strength and high stiffness. These standards are designed to ensure that the window glass can effectively resist external impacts during daily driving and provide a solid safety barrier for passengers in the car. In view of current technological trends, the research and development of window glass focuses on the dual goals of lightweighting and improving strength to optimize the overall performance and safety of the vehicle.
[0004] However, in extreme driving conditions, such as in emergencies such as car accidents or vehicles falling into water, traditional high-strength car window glass may become an obstacle to escape and endanger the lives of passengers because it is difficult to break quickly.
[0005] Therefore, it is necessary to provide an impact-resistant laminated glass and a preparation process to solve the above technical problems. Summary of the invention
[0006] The present invention overcomes the deficiencies of the prior art and provides an impact-resistant laminated glass and a preparation process thereof.
[0007] To achieve the above object, the technical solution adopted by the present invention is: a process for preparing impact-resistant laminated glass, comprising the following steps:
[0008] S1. Provide three pieces of glass of the same size and different thicknesses, which are used as the first glass layer, the second glass layer and the third glass layer respectively, and clean and surface treat them;
[0009] S2, preparing two polyvinyl butyral substrates, dispersing carbon nanotubes therein respectively, to obtain two polyvinyl butyral / carbon nanotube composite solutions, which are used as stress concentration layer materials and stress diffusion layer materials respectively;
[0010] S3, coating the stress concentration layer material and the stress diffusion layer material prepared in step S2 on two sides of the third glass layer respectively to obtain a composite intermediate layer;
[0011] S4, applying an adhesive additive on one side of the first glass layer and the second glass layer, aligning the edges of the first glass layer, the composite intermediate layer and the third glass layer and stacking them in sequence to obtain a three-layer structure, wherein the stress concentration layer is between the first glass layer and the third glass layer, and the stress diffusion layer is between the third glass layer and the second glass layer;
[0012] S5. Pre-evacuate the three-layer structure obtained in step S4 to remove air between the layers, place the three-layer structure in an autoclave for reaction, and obtain impact-resistant laminated glass after cooling.
[0013] In a preferred embodiment of the present invention, in S1, the thicknesses of the first glass layer, the second glass layer and the third glass layer are 0.8-1.1 mm, 1.2-1.8 mm and 0.6-0.9 mm respectively.
[0014] In a preferred embodiment of the present invention, in said S2, the method for preparing the stress concentration layer material comprises the following steps:
[0015] S21, adding polyvinyl butyral resin to a solvent, heating to dissolve and stirring to obtain a uniform polyvinyl butyral solution;
[0016] S22, after pre-treating the carbon nanotubes, dispersing them in a solvent, adding a silane coupling agent, reacting at a temperature of 60 to 75° C. for 15 to 35 minutes, and then drying;
[0017] S23. Add the dried carbon nanotubes into the polyvinyl butyral solution, stir and mix them at a low speed for 2 to 5 minutes, let them stand for 20 to 30 minutes, and then use an ultrasonic disperser to perform ultrasonic treatment for 15 to 30 minutes to obtain a stress concentration layer material, wherein the mass ratio of the carbon nanotubes is 1.2wt% to 2.5wt%.
[0018] In a preferred embodiment of the present invention, in S2, the method for preparing the stress diffusion layer material comprises the following steps:
[0019] S24, adding polyvinyl butyral resin to the solvent, heating to dissolve and stirring to obtain a uniform polyvinyl butyral solution;
[0020] S25, adding the carbon nanotube powder and the dispersant to the polyvinyl butyral solution, and preliminarily mixing them with a high-speed stirrer for 2 to 5 minutes to obtain a mixed solution;
[0021] S26. Use an ultrasonic disperser to ultrasonically treat the mixed solution for 90 to 120 minutes, and then perform vacuum degassing to obtain a stress concentration layer material, wherein the mass ratio of the carbon nanotubes is 0.5 wt% to 1.0 wt%.
[0022] In a preferred embodiment of the present invention, in S5, the temperature in the autoclave is controlled at 135-150°C, the pressure is controlled at 0.7-1.5 MPa, and the reaction time is 1.2-1.8 h.
[0023] In a preferred embodiment of the present invention, in S4, the thickness ratio of the stress concentration layer, the third glass layer and the stress diffusion layer is 0.6-1:1:1-1.5.
[0024] An impact-resistant laminated glass, prepared based on any one of the above-mentioned processes for preparing an impact-resistant laminated glass, comprising: a first glass layer, a second glass layer, and a composite intermediate layer arranged between the first glass layer and the second glass layer; the first glass layer has a thickness of 0.8 to 1.1 mm, and the second glass layer has a thickness of 1.2 to 1.8 mm;
[0025] The composite intermediate layer includes a stress concentration layer, a stress diffusion layer and a third glass layer arranged between the stress concentration layer and the stress diffusion layer; the stress concentration layer is arranged between the first glass layer and the third glass layer, and the stress diffusion layer is arranged between the second glass layer and the third glass layer; the thickness of the third glass layer is 0.6 to 0.9 mm, and the thickness ratio among the stress concentration layer, the third glass layer and the stress diffusion layer is 0.6 to 1:1:1 to 1.5.
[0026] In a preferred embodiment of the present invention, the first glass layer, the second glass layer and the third glass layer are one or more of tempered glass, soda-lime glass, high-aluminum glass or heat-strengthened glass.
[0027] In a preferred embodiment of the present invention, the stress concentration layer or the stress diffusion layer further comprises: at least one of an antioxidant, an ultraviolet absorber, an infrared absorber, and a plasticizer.
[0028] In a preferred embodiment of the present invention, a bonding agent is provided on the contact surfaces of the first glass layer, the second glass layer and the composite intermediate layer, and a bonding agent is also provided on the contact surfaces of the stress concentration layer, the stress diffusion layer and the third glass layer.
[0029] The present invention solves the defects existing in the background technology and has the following beneficial effects:
[0030] (1) The present invention provides an impact-resistant laminated glass and a preparation process, comprising a first glass layer, a second glass layer and a composite intermediate layer arranged between the first glass layer and the second glass layer, wherein the composite intermediate layer comprises a stress concentration layer, a stress diffusion layer and a third glass layer arranged between the stress concentration layer and the stress diffusion layer; the second glass layer, as the outer side of the vehicle window, has excellent impact resistance with the assistance of the stress diffusion layer, while the first glass layer, as the inner side of the vehicle window, can be easily broken from inside the vehicle with the assistance of the stress concentration layer, thereby ensuring the safety of the vehicle and facilitating self-rescue of the driver and passengers in extreme driving environments, thereby protecting the lives of passengers.
[0031] (2) In the present invention, by precisely controlling the mass ratio and dispersion degree of carbon nanotubes, stress concentration layers and stress diffusion layers with completely different properties are prepared and arranged on both sides of the third glass layer, respectively, to form an asymmetric impact resistance, low impact resistance from the first glass layer side, and high impact resistance from the second glass layer side. That is, when used as a vehicle window, it has excellent external impact resistance and can shatter the entire piece of impact-resistant laminated glass from inside the vehicle in an emergency, thereby ensuring the safety of the occupants in the vehicle.
[0032] (3) In the present invention, the stress concentration layer is relatively thin, and the third glass layer is also thinner than the first glass layer and the second glass layer. When the first glass layer is impacted, the stress concentration layer will act as a "trigger point" to concentrate the impact energy and transfer it to the third glass layer, accelerating its breaking process, thereby causing a sudden stress change from the first glass layer to the second glass layer. At the same time, due to the breaking of the third glass layer, the stress diffusion layer will be synchronously deformed and broken, thereby reducing its stress diffusion effect. This design allows the entire glass to be broken from the inside more quickly in an emergency, providing an escape route for people in the car. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.
[0034] Figure 1 is a schematic diagram of the structure of impact-resistant laminated glass in a preferred embodiment of the present invention;
[0035] Figure 2 This is a process flow for preparing impact-resistant laminated glass according to a preferred embodiment of the present invention;
[0036] In the figure: 100, a first glass layer; 200, a second glass layer; 300, a composite intermediate layer; 310, a stress concentration layer; 320, a stress diffusion layer; 330, a third glass layer. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0039] In the description of the present application, it should be understood that the terms "center", "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the scope of protection of the present application. In addition, the terms "first", "second", etc. are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, features defined as "first", "second", etc. may explicitly or implicitly include one or more of the features. In the description of the invention, unless otherwise specified, "multiple" means two or more.
[0040] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be directly connected or indirectly connected through an intermediate medium, and it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood by specific circumstances.
[0041] like Figure 2 As shown, the present invention provides a process for preparing impact-resistant laminated glass, comprising the following steps:
[0042] S1. Provide three pieces of glass with the same size and different thicknesses, respectively serving as a first glass layer 100, a second glass layer 200 and a third glass layer 330, and clean and perform surface treatment on them.
[0043] S2. Prepare two polyvinyl butyral substrates, disperse carbon nanotubes therein respectively, and obtain two polyvinyl butyral / carbon nanotube composite solutions, which are used as the material of the stress concentration layer 310 and the material of the stress diffusion layer 320 respectively.
[0044] S3 . Coat the stress concentration layer 310 material and the stress diffusion layer 320 material prepared in step S2 on two surfaces of the third glass layer 330 , respectively, to obtain a composite intermediate layer 300 .
[0045] S4. Apply a bonding agent on one side of the first glass layer 100 and the second glass layer 200, align the edges of the first glass layer 100, the composite intermediate layer 300 and the third glass layer 330 and stack them in sequence to obtain a three-layer structure, wherein the stress concentration layer 310 is between the first glass layer 100 and the third glass layer 330, and the stress diffusion layer 320 is between the third glass layer 330 and the second glass layer 200.
[0046] S5. Pre-evacuate the three-layer structure obtained in step S4 to remove air between the layers, place the three-layer structure in an autoclave for reaction, and obtain impact-resistant laminated glass after cooling.
[0047] The glass raw material in step S1 can be one or more of tempered glass, soda-lime glass, high-aluminum glass or heat-strengthened glass. In actual use, the first glass layer 100, the second glass layer 200 and the third glass layer 330 preferably use the same glass to reduce costs and avoid confusion in preparation. In some embodiments, aluminosilicate glass or borosilicate glass can also be used as the first glass layer 100, the second glass layer 200 and the third glass layer 330.
[0048] The first glass layer 100 is designed to be thinner, 0.8 to 1.1 mm, to adapt to the rapid response during internal impact, and serves as the inner side of the window; the second glass layer 200 has a thickness range of 1.2 to 1.8 mm, and serves as the outer side of the window, as the main load-bearing protective layer; the third glass layer 330 has a thickness range of 0.6 to 0.9 mm, and serves as a key layer for connection and stress regulation.
[0049] Furthermore, the first glass layer 100 , the second glass layer 200 and the third glass layer 330 are subjected to a strict cleaning process to remove surface impurities, and their surface adhesion is enhanced through surface treatment technology (such as chemical etching or plasma treatment) to facilitate subsequent interlayer bonding.
[0050] In step S2, the method for preparing the material of the stress concentration layer 310 includes the following steps:
[0051] S21. Add polyvinyl butyral resin to ethanol or butanol solvent, heat to dissolve and stir to obtain a uniform polyvinyl butyral solution; it is worth noting that at least 30g of polyvinyl butyral resin can be dissolved in 100g of ethanol. During the dissolution process, the polyvinyl butyral resin is added while stirring. Agglomeration is avoided when adding the materials, because the dissolution time of the polyvinyl butyral resin after agglomeration will increase several times. The stirring process is summarized, and the dissolution time is shortened by heating to 30-40°C to ensure that a clear and transparent polyvinyl butyral solution is obtained.
[0052] S22. Pre-treating the carbon nanotubes includes ultrasonic dispersion and pickling to remove surface impurities and defects and increase the active points on the surface; dispersing the pre-treated carbon nanotubes in a solvent, adding a silane coupling agent, reacting at a temperature of 60 to 75°C for 15 to 35 minutes, and then drying. The silane coupling agent will chemically react with the active points on the surface of the carbon nanotubes to form chemical bonds and enhance the mutual force between the carbon nanotube particles.
[0053] Further, the silane coupling agent includes one or more of a vinyl silane coupling agent, a methacrylic silane coupling agent, an aminopropyl silane coupling agent, a mercapto silane coupling agent, an epoxy silane coupling agent and a cyano silane coupling agent.
[0054] S23, adding the dried carbon nanotubes to the polyvinyl butyral solution, stirring at a low speed to mix for 2 to 5 minutes, standing for 20 to 30 minutes, and then using an ultrasonic disperser to ultrasonically treat the solution for 15 to 30 minutes to obtain a stress concentration layer 310 material, wherein the mass ratio of the carbon nanotubes is 1.2wt% to 2.5wt%.
[0055] In step S23, low-speed stirring is used to preliminarily disperse the carbon nanotubes in the polyvinyl butyral solution. During the static process, the modified carbon nanotubes agglomerate to promote the formation of carbon nanotube agglomerates. The subsequent brief ultrasonic dispersion is to evenly disperse the carbon nanotube agglomerates in the polyvinyl butyral matrix. In the stress concentration layer 310 material prepared by the above steps, independent agglomerates are formed, which can effectively transfer and concentrate stress.
[0056] Furthermore, the carbon nanotubes in this embodiment are multi-walled carbon nanotubes. Due to the high strength and modulus of multi-walled carbon nanotubes, they can withstand large stresses without being damaged, thereby effectively improving the stress concentration effect of the material, allowing the material to reach the damage limit faster and break or shatter when impacted.
[0057] The method for preparing the material of the stress diffusion layer 320 comprises the following steps:
[0058] S24. Add polyvinyl butyral resin to ethanol or butanol solvent, heat to dissolve and stir to obtain a uniform polyvinyl butyral solution; it is worth noting that at least 30g of polyvinyl butyral resin can be dissolved in 100g of ethanol. During the dissolution process, the polyvinyl butyral resin is added while stirring. Agglomeration is avoided when adding the materials, because the dissolution time of the polyvinyl butyral resin after agglomeration will increase several times. The stirring process is summarized, and the dissolution time is shortened by heating to 30-40°C to ensure that a clear and transparent polyvinyl butyral solution is obtained.
[0059] S25, adding the carbon nanotube powder and the dispersant to the polyvinyl butyral solution, and preliminarily mixing them with a high-speed stirrer for 2 to 5 minutes to obtain a mixed solution, wherein the dispersant comprises at least one of polyvinyl pyrrolidone, polyethylene glycol, polyacrylic acid, sodium dodecylbenzene sulfonate or sodium dodecyl sulfate.
[0060] S26, using an ultrasonic disperser to perform ultrasonic treatment on the mixed solution for 90 to 120 minutes, and then performing vacuum degassing to obtain a stress concentration layer 310 material, wherein the mass ratio of the carbon nanotubes is 0.5 wt% to 1.0 wt%.
[0061] It is worth noting that the ultrasonic treatment for a long time can generate local high pressure and micro jets by using the cavitation effect of ultrasound, which can fully break the interaction between carbon nanotubes, reduce the agglomeration of carbon nanotubes, and make them more evenly dispersed in the polyvinyl butyral solution. A small amount of carbon nanotubes are evenly dispersed in the polyvinyl butyral matrix, forming an effective stress transfer path, and the good interface bonding between carbon nanotubes and polyvinyl butyral materials constitutes the main channel for stress diffusion. The interface diffusion phenomenon enables stress to be quickly transferred and dispersed along the interface with carbon nanotubes, thereby reducing the stress concentration inside the material, reducing the risk of material damage, and improving its impact resistance.
[0062] In step S4, the thickness ratio between the stress concentration layer 310, the third glass layer 330 and the stress diffusion layer 320 is 0.6-1:1:1-1.5. The stress concentration layer 310 is relatively thin, and the third glass layer 330 is also thinner than the first glass layer 100 and the second glass layer 200. When the first glass layer 100 is impacted, the stress concentration layer 310 will act as a "trigger point" to concentrate and transfer the impact energy to the third glass layer 330, accelerating its breaking process, thereby causing a sudden stress change from the first glass layer 100 to the second glass layer 200. At the same time, due to the breaking of the third glass layer 330, the stress diffusion layer 320 is synchronously deformed and broken, thereby reducing its stress diffusion effect. This design allows the entire glass to be broken from the inside more quickly in an emergency (such as when escaping), providing an escape route for people in the car.
[0063] In the present invention, by precisely controlling the mass ratio and dispersion of carbon nanotubes, a stress concentration layer 310 and a stress diffusion layer 320 with completely different properties are prepared, which are respectively arranged on both sides of the third glass layer 330, forming an asymmetric impact resistance, low impact resistance from the first glass layer 100 side, and high impact resistance from the second glass layer 200 side, that is, when used as a vehicle window, it has excellent external impact resistance, and can shatter the entire piece of impact-resistant laminated glass from inside the vehicle in an emergency, thereby ensuring the safety of the drivers and passengers in the vehicle.
[0064] In step S5, the temperature in the autoclave is controlled at 135-150°C, the pressure is controlled at 0.7-1.5 MPa, and the reaction time is 1.2-1.8 hours. The high temperature and high pressure environment is used to accelerate the curing of the adhesive layer, improve the bonding strength between the layers, and ensure the stability and durability of the entire structure.
[0065] like Figure 1 As shown, the present invention also provides an impact-resistant laminated glass, comprising: a first glass layer 100, a second glass layer 200 and a composite intermediate layer 300 arranged between the first glass layer 100 and the second glass layer 200; the thickness of the first glass layer 100 is 0.8-1.1 mm, and the thickness of the second glass layer 200 is 1.2-1.8 mm; the composite intermediate layer 300 comprises a stress concentration layer 310, a stress diffusion layer 320 and a third glass layer 330 arranged between the stress concentration layer 310 and the stress diffusion layer 320; the stress concentration layer 310 is arranged between the first glass layer 100 and the third glass layer 330, and the stress diffusion layer 320 is arranged between the second glass layer 200 and the third glass layer 330; the thickness of the third glass layer 330 is 0.6-0.9 mm, and the thickness ratio between the stress concentration layer 310, the third glass layer 330 and the stress diffusion layer 320 is 0.6-1:1:1-1.5.
[0066] The first glass layer 100, the second glass layer 200 and the third glass layer 330 are one or more of tempered glass, soda-lime glass, high-aluminum glass or heat-strengthened glass. In actual use, the first glass layer 100, the second glass layer 200 and the third glass layer 330 preferably use the same glass to reduce costs and avoid confusion in preparation. In some embodiments, aluminosilicate glass or borosilicate glass can also be used as the first glass layer 100, the second glass layer 200 and the third glass layer 330.
[0067] The stress concentration layer 310 or the stress diffusion layer 320 further includes: at least one of an antioxidant, an ultraviolet absorber, an infrared absorber, and a plasticizer. These additives are used to improve the service life, ultraviolet absorption rate, heat insulation and weather resistance of the impact-resistant laminated glass. In some embodiments, other functional additives may be added to improve the performance of the vehicle window of the impact-resistant laminated glass.
[0068] The contact surfaces of the first glass layer 100, the second glass layer 200 and the composite intermediate layer 300 are provided with an adhesive agent, and the contact surfaces of the stress concentration layer 310, the stress diffusion layer 320 and the third glass layer 330 are also provided with an adhesive agent; the adhesive agent includes one or more of a vinyl silane coupling agent, a methyl acrylic silane coupling agent, an aminopropyl silane coupling agent, a mercapto silane coupling agent, an epoxy silane coupling agent and a cyano silane coupling agent. Example
[0069] Step 1: Use soda-lime glass to prepare a plurality of first glass layers 100, second glass layers 200 and third glass layers 330 with a length and width of 120*180 mm, wherein the thickness of the first glass layer 100 is 0.8 mm and 1.1 mm, the thickness of the second glass layer 200 is 1.2 mm and 1.8 mm, and the thickness of the third glass layer 330 is 0.6 mm and 0.9 mm, and clean and treat their surfaces.
[0070] Step 2: preparing the stress concentration layer 310 material, including the following steps:
[0071] 1. Add polyvinyl butyral resin into ethanol solvent, heat to 35°C to dissolve and stir to obtain a uniform polyvinyl butyral solution;
[0072] 2. Ultrasonic dispersion and acid washing of carbon nanotubes were performed, and then they were dispersed in an ethanol solvent, a mercaptosilane coupling agent was added, and the mixture was reacted at 70° C. for 25 min and then dried;
[0073] 3. Add the dried carbon nanotubes to the polyvinyl butyral solution, stir at a low speed to mix for 4 minutes, let it stand for 30 minutes, and then use an ultrasonic disperser to ultrasonically treat it for 30 minutes to obtain a stress concentration layer 310 material with a carbon nanotube mass ratio of 0.8wt%, 1.2wt%, 1.8wt%, 2.5wt% and 3wt%.
[0074] The first glass layer 100, the stress concentration layer 310 and the third glass layer 330 are combined to prepare a laminated glass sample, and according to the impact resistance test conditions in GB9656, a 227g steel ball is selected to perform a drop test, the drop impact surface is the outer surface of the first glass layer 100, and the maximum height that the laminated glass sample can withstand without breaking is recorded. The test results are described in Table 1 below.
[0075] Table 1. Stress concentration layer 310 material performance test
[0076]
[0077] It can be concluded from the above test results that in the laminated glass composed of the first glass layer 100, the stress concentration layer 310 and the third glass layer 330 of uniform thickness, different carbon nanotube mass ratios perform differently in the impact resistance test, and when the carbon nanotube mass ratio in the stress concentration layer 310 is between 1.2 and 2.5 wt%, the stress concentration effect is best.
[0078] Step 3: preparing the stress diffusion layer 320 material, including the following steps:
[0079] 1. Add polyvinyl butyral resin into ethanol solvent, heat to 35°C to dissolve and stir to obtain a uniform polyvinyl butyral solution;
[0080] 2. Add the carbon nanotube powder and polyvinyl pyrrolidone into the polyvinyl butyral solution, and use a high-speed stirrer to preliminarily mix them for 4 minutes to obtain a mixed solution.
[0081] 3. The mixed solution was ultrasonically treated for 110 minutes using an ultrasonic disperser, and then vacuum degassing was performed to obtain stress diffusion layer 320 materials with carbon nanotube mass ratios of 0wt%, 0.5wt%, 1.0wt%, 1.5wt% and 1.9wt%.
[0082] The second glass layer 200, the stress diffusion layer 320 and the third glass layer 330 are combined to prepare a laminated glass sample, and according to the impact resistance test conditions in GB9656, a 227g steel ball is selected to perform a drop test, the drop impact surface is the outer surface of the second glass layer 200, and the maximum height that the laminated glass sample can withstand without breaking is recorded. The test results are described in Table 2 below.
[0083] Table 2. Stress diffusion layer 320 material performance test
[0084]
[0085] It can be concluded from the above test results that in the laminated glass composed of the second glass layer 200, the stress diffusion layer 320 and the third glass layer 330 of uniform thickness, different carbon nanotube mass ratios show different performances in the impact resistance test. When the carbon nanotube mass ratio in the stress diffusion layer 320 is between 0.5 and 1.0 wt%, the stress diffusion effect is optimal and the impact resistance is the best.
[0086] Step 4: Combine the above-mentioned first glass layer 100, second glass layer 200, third glass layer 330, stress concentration layer 310 and stress diffusion layer 320 into laminated glass samples. The thickness of automobile window glass is generally between 3 and 5 mm. In this experiment, laminated glass with a thickness of nearly 4.5 mm was prepared for the experiment, wherein the mass ratio of carbon nanotubes in the stress concentration layer 310 was 1.8wt%, and the mass ratio of carbon nanotubes in the stress diffusion layer 320 was 0.5wt%. According to the impact resistance test conditions in GB9656, a 227g steel ball was selected for the drop test. The drop impact surfaces were the outer surfaces of the first glass layer 100 and the second glass layer 200, respectively. The maximum height that the laminated glass can withstand without breaking was recorded. The test results of the laminated glass samples are shown in Table 3:
[0087] Table 3. Laminated glass sample test results
[0088]
[0089] From the above test results, it can be concluded that the impact test results of the second glass layer 200 side of sample 12 and sample 17 are the best, and the impact resistance performance difference between the first glass layer 100 and the second glass layer 200 is the largest. In sample 12, the thickness ratio of the stress concentration layer 310, the third glass layer 330 and the stress diffusion layer 320 is about 0.84:1:1.34, and in sample 17, the thickness ratio of the stress concentration layer 310, the third glass layer 330 and the stress diffusion layer 320 is about 0.67:1:1. It can be concluded that in the laminated glass structure, the thickness of the first glass layer 100 is 0.8-1.1 mm, the thickness of the second glass layer 200 is 1.2-1.8 mm, and the thickness of the third glass layer 330 is The thickness of the stress concentration layer 310, the third glass layer 330 and the stress diffusion layer 320 is controlled to be 0.6-1:1:1-1.5, so as to achieve the best asymmetry of the impact resistance, retaining the high impact resistance of the second glass layer 200 and having the low impact resistance of the first glass layer 100. This design enables the whole glass to be broken more quickly from the inside in an emergency (such as when escaping), thereby providing an escape route for the people in the car.
[0090] Furthermore, according to the GB9656 method, the human head model impact, penetration resistance and impact resistance tests were performed on Sample 12 and Sample 17, respectively. In the test results, Y means passing the test, and X means failing the test. The test results are shown in Table 4.
[0091] Table 4. Performance test table of sample 12 and sample 17
[0092]
[0093] The preferred samples 12 and 17 of the present invention have passed the human head model impact, penetration resistance and impact resistance tests, and meet the automotive glass safety test specifications. The impact-resistant laminated glass provided by the present invention has a wide range of application prospects in high-safety level vehicles.
[0094] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.
Claims
1. A process for preparing impact-resistant laminated glass, characterized in that: The following steps are involved: S1. Provide three pieces of glass of the same size and different thicknesses, respectively serving as the first glass layer, the second glass layer and the third glass layer, and clean and surface treat them; wherein the thicknesses of the first glass layer, the second glass layer and the third glass layer are 0.8-1.1 mm, 1.2-1.8 mm and 0.6-0.9 mm respectively; S2, preparing two polyvinyl butyral substrates, dispersing carbon nanotubes therein respectively, to obtain two polyvinyl butyral / carbon nanotube composite solutions, which are used as stress concentration layer materials and stress diffusion layer materials respectively; The method for preparing the stress concentration layer material comprises the following steps: S21, adding polyvinyl butyral resin to a solvent, heating to dissolve and stirring to obtain a uniform polyvinyl butyral solution; S22, after pre-treating the carbon nanotubes, dispersing them in a solvent, adding a silane coupling agent, reacting at a temperature of 60 to 75° C. for 15 to 35 minutes, and then drying; S23, adding the dried carbon nanotubes to the polyvinyl butyral solution, stirring at a low speed to mix for 2 to 5 minutes, standing for 20 to 30 minutes, and then using an ultrasonic disperser to ultrasonically treat the solution for 15 to 30 minutes to obtain a stress concentration layer material, wherein the mass ratio of the carbon nanotubes is 1.2wt% to 2.5wt%; The method for preparing the stress diffusion layer material comprises the following steps: S25, adding the carbon nanotube powder and the dispersant to the polyvinyl butyral solution, and preliminarily mixing them with a high-speed stirrer for 2 to 5 minutes to obtain a mixed solution; S26, using an ultrasonic disperser to ultrasonically treat the mixed solution for 90 to 120 minutes, and then performing vacuum degassing to obtain a stress diffusion layer material, wherein the mass ratio of the carbon nanotubes is 0.5 wt% to 1.0 wt%; S3, coating the stress concentration layer material and the stress diffusion layer material prepared in step S2 on two sides of the third glass layer respectively to obtain a composite intermediate layer; S4, applying an adhesive additive on one side of the first glass layer and the second glass layer, aligning the edges of the first glass layer, the composite intermediate layer and the third glass layer and stacking them in sequence to obtain a three-layer structure, wherein the stress concentration layer is between the first glass layer and the third glass layer, and the stress diffusion layer is between the third glass layer and the second glass layer; S5. Pre-evacuate the three-layer structure obtained in step S4 to remove air between the layers, place the three-layer structure in an autoclave for reaction, and obtain impact-resistant laminated glass after cooling.
2. The impact-resistant laminated glass and preparation process according to claim 1, characterized in that: In S5, the temperature in the autoclave is controlled at 135-150°C, the pressure is controlled at 0.7-1.5 MPa, and the reaction time is 1.2-1.8 hours.
3. The impact-resistant laminated glass and preparation process according to claim 1, characterized in that: In the above S4, the thickness ratio of the stress concentration layer, the third glass layer and the stress diffusion layer is 0.6-1:1:1-1.
5.
4. An impact-resistant laminated glass, prepared according to the preparation process of an impact-resistant laminated glass according to any one of claims 1 to 3, characterized in that: include: A first glass layer, a second glass layer, and a composite intermediate layer disposed between the first glass layer and the second glass layer; the first glass layer has a thickness of 0.8 to 1.1 mm, and the second glass layer has a thickness of 1.2 to 1.8 mm; The composite intermediate layer includes a stress concentration layer, a stress diffusion layer and a third glass layer arranged between the stress concentration layer and the stress diffusion layer; the stress concentration layer is arranged between the first glass layer and the third glass layer, and the stress diffusion layer is arranged between the second glass layer and the third glass layer; the thickness of the third glass layer is 0.6 to 0.9 mm, and the thickness ratio among the stress concentration layer, the third glass layer and the stress diffusion layer is 0.6 to 1:1:1 to 1.
5.
5. The impact-resistant laminated glass according to claim 4, characterized in that: The first glass layer, the second glass layer and the third glass layer are one or more of tempered glass, soda-lime glass, high-aluminum glass or heat-strengthened glass.
6. The impact-resistant laminated glass according to claim 4, characterized in that: The stress concentration layer or the stress diffusion layer further includes at least one of an antioxidant, an ultraviolet absorber, an infrared absorber, and a plasticizer.
7. The impact-resistant laminated glass according to claim 4, characterized in that: The contact surfaces of the first glass layer, the second glass layer and the composite intermediate layer are provided with a bonding agent, and the contact surfaces of the stress concentration layer, the stress diffusion layer and the third glass layer are also provided with a bonding agent.
Citation Information
Patent Citations
Strengthened glass and glass laminates having asymmetric impact resistance
CN104220252A
Laminated glass and preparation method thereof
CN111847906A
Cited By
Intelligent preparation system and method for composite tempered glass
CN120439665A
A smart manufacturing system and method for composite tempered glass
CN120439665B